Comparison between the effects of zilpaterol hydrochloride and Rsalbutamol during the finishing period on the growth performance and carcass characteristics of feedlot cattle - Webb, E.C. (Edward Cottington) (University of Pretoria, 2022)
Dissertation (MSc (Agric Animal Science (Production Physiology and Product Quality))--University of Pretoria, 2021.